Five countries, five models: A comparison of fiscal frameworks and lessons for Finland - Iain Begg; Tero Kuusi; Olavi Kylliäinen (The Research Institute of the Finnish Economy (ETLA), 2023)
In recent years, many countries have sought to transform their fiscal frameworks, with the aim of rendering their public finances more sustainable and preventing the emergence of fiscal problems. This report presents the findings of comparative research into the fiscal frameworks of five countries (Denmark, Ireland, the Netherlands, New Zealand and Sweden). All five countries have developed effective fiscal frameworks in the last two decades, and it is evident that they reflect both reactions to past episodes of fiscal laxity and the fostering of a broad consensus on the necessity of a more disciplined and robust framework. There are noteworthy differences of approach, with the implication that rather than there being an optimal framework, successful ones can take different forms. It is never easy to transplant what works in one national setting to another, but there are several insights from experience in the comparator countries which could help to enhance the Finnish fiscal framework.
Keywords: E62; H30; H61; P52; 330; Fiscal policy; Fiscal rules; Expenditure ceilings